(untitled) (Texas Journal of Medical Science, 2023)
Pulmonary fibrosis, a progressive and debilitating lung disease, has long been the focus of extensive research due to its impact on respiratory function. However, emerging studies have unveiled a lesser-explored facet of this disease: its influence on extrapulmonary organs. This article delves into the uncharted territory of the impact of pulmonary fibrosis on the structure of the small intestine. Through a comprehensive review of experimental data and clinical observations, it becomes evident that pulmonary fibrosis is not merely confined to the lungs. Rather, it exerts a multifaceted influence on the small intestine, leading to structural alterations, impaired nutrient absorption, and a cascade of systemic effects. Understanding this interplay between the lung and the intestine is pivotal for a holistic comprehension of pulmonary fibrosis and opens new avenues for therapeutic strategies targeting extrapulmonary manifestations